Smart Healthcare in Urban Contexts: A Bibliometric Review and Managerial Implications (European journal of volunteering and community-based projects, 2025)
Purpose: This research aims to evaluate existing literature about smart cities in healthcare settings while determining potential future research paths. The research examines digital transformation effects on healthcare delivery as well as healthcare governance and policy within urban environments.Design/methodology/approach: The research study adopts a structured literature review approach that combines bibliometric and content analysis. The Scopus database provided 617 peer-reviewed articles for this study. The authors conducted multiple screening stages before selecting 48 articles for thorough evaluation using VOSviewer and thematic content coding.Findings: The analysis shows that the existing research about this topic remains scattered and continues to develop without clear connections between studies. The research identified three main research areas, which include smart cities for health safety, smart cities for health data sharing, and smart cities for developing healthcare skills. The research reveals important managerial and policy implications that healthcare systems can use to boost their performance and resilience through smart urban innovation.Originality: This paper creates a first-of-its-kind bibliometric map of smart healthcare research in urban areas to present an integrated view of technological managerial and policy-oriented contributions. The research fills an important knowledge gap by establishing a connection between digital health approaches and urban governance frameworks.Practical implications: The study delivers data-driven guidance for healthcare managers and urban policymakers who want to establish smart health solutions through evidence-based strategic decision support and investment planning and policy development.
Keywords: Smart city, Smart healthcare, Digital transformation, Healthcare management, Urban governance, Bibliometric review, Policy implications.